Analysis of neonatal sepsis in one neonatal intensive care unit for 6 years - Peter Chun; Seom Gim Kong; Shin Yun Byun; Su Eun Park; Hyung Du Lee (Korean Pediatric Society, 2010)
Purpose : Sepsis is a significant cause of morbidity and mortality in the newborn, particularly in preterm. The objective of this study was to analyze the incidence rate, causative pathogens and clinical features of neonatal sepsis in one neonatal intensive care unit (NICU) for 6 years. Methods : This study was retrospectively performed to review the clinical and laboratory characteristics including sex, gestational age, birth weight, Apgar score, length of hospitalization, length of total parenteral nutrition, presence of central venous catheter, underlying diseases, laboratory findings, microorganisms isolated from blood culture, complications and mortality in 175 patients between January 2003 and December 2008. Results : 1) Sepsis was present in 175 of 3,747 infants for 6 years. There were more gram-positive organisms. 2) The gram-negatives were more prevalent in preterm. There were no significant differences of other clinical features between two groups. 3) Underlying diseases were found in 73.7%, and the most common disease was cardiovascular disease. The most common organisms of gram-positives and gram-negatives were methicillin resistant Staphylococcus aureus (MRSA) and Serratia marcescens. 4) There was statistically significant difference on platelet counts between two groups (P<0.05). 5) Complications were found in 18.3% and septic shock was the most common. MRSA was the most common pathogen in sepsis with complication. 6) The mortality rate was 7.4%. 7) There were differences in monthly blood stream infection/ 1,000 patient-days. Conclusion : The studies about the factors that can influence neonatal sepsis will contribute to decrease the infection rates in NICUs.